2009
DOI: 10.1126/science.1165187
|View full text |Cite
|
Sign up to set email alerts
|

Draxin, a Repulsive Guidance Protein for Spinal Cord and Forebrain Commissures

Abstract: Axon guidance proteins are critical for the correct wiring of the nervous system during development. Several axon guidance cues and their family members have been well characterized. More unidentified axon guidance cues are assumed to participate in the formation of the extremely complex nervous system. We identified a secreted protein, draxin, that shares no homology with known guidance cues. Draxin inhibited or repelled neurite outgrowth from dorsal spinal cord and cortical explants in vitro. Ectopically exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
200
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(219 citation statements)
references
References 15 publications
6
200
0
Order By: Relevance
“…Recent studies have shown that draxin is a repulsive guidance cue involved in commissural axon projection in the developing nervous system (60). Interestingly, draxin binds multiple netrin receptors: DCC, neurogenin, UNC5, and DSCAM, and the interaction of draxin and DCC is required for draxin-mediated neurite outgrowth and guidance (61).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that draxin is a repulsive guidance cue involved in commissural axon projection in the developing nervous system (60). Interestingly, draxin binds multiple netrin receptors: DCC, neurogenin, UNC5, and DSCAM, and the interaction of draxin and DCC is required for draxin-mediated neurite outgrowth and guidance (61).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we recently demonstrated that cingulate callosal axons also express the axon guidance receptor DCC, and that these axons are attracted towards its ligand, NTN1, at the midline (Fothergill et al, 2014). Similarly, other short-and longrange axon guidance molecules have been demonstrated to function in regulating neocortical callosal pathfinding (Shu and Richards, 2001;Shu et al, 2003;Andrews et al, 2006;Islam et al, 2009;Nishikimi et al, 2011). As callosal axons from the dorso-lateral cortex, where Nrp1 expression is absent, are able to project their axons medially (Zhou et al, 2013), it appears likely that other axon guidance mechanisms can guide callosal pathfinding in the absence of Nrp1 expression.…”
Section: Emx1 Mediates Cingulate Callosal Axon Guidance By Regulatingmentioning
confidence: 99%
“…S7A-F). Midline guidance cues Sema3c (Niquille et al, 2009;Piper et al, 2009b), Netrin1 (Serafini et al, 1996) and Draxin (Islam et al, 2009) were expressed normally in Nf2 mutants (supplementary material Fig. S7G-L).…”
Section: Upregulation Of Slit2 Contributes To Callosal Agenesis In Nfmentioning
confidence: 99%